(untitled) (Research, Society and Development, 2022)
Coronavirus disease 2019 (COVID-19) is an acute infectious respiratory disease caused by a novel coronavirus causing severe acute respiratory syndrome 2 (SARS-CoV-2). The infection primarily affects epithelial/alveolar and endothelial cells, resulting in desquamation of pneumocytes, presence of hyaline membrane, formation and interstitial inflammation with lymphocyte infiltration. Due to these pathophysiological changes, symptoms may range from mild, such as a cold and transient anosmia, to severe respiratory failure, leading to the need for ventilatory support. Currently, one of the forms of therapeutic intervention in COVID-19 is based on the use of Invasive Mechanical Ventilation (IMV) or not, in both forms artificial ventilation is achieved with the application of positive airway pressure being its difference given in the use of a nasotracheal and orotracheal prosthesis. However, factors related to the patient or to the use of the ventilator itself may trigger pulmonary complications such as barotrauma or infections. The aim of this study was to describe the main complications of IMV in patients on COVID-19. To this end, a literature review was conducted on the pulmonary impacts of IMV in cases of covid aiming to highlight the need for correct performance of the procedure in order to reduce the number of cases reported on the subject.